PRAKTIK MULTIKULTURALISME DI LEMBAGA PRAMUKA: STUDI KASUS KEGIATAN LOMBA TINGKAT TIGA (LT 3) KWARCAB SIDOARJO - Muhammad Zulio Hidayatul Fatah; Luluk Fikri Zuhriyah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study examines the practice of multiculturalism in the Three-Level Competition (LT 3) of the Sidoarjo Scout Movement, focusing on cross-cultural interactions, the role of mentors, and participant dynamics. Using a qualitative case study approach, data were collected through semi-structured interviews, participatory observations, and document analysis involving 13 participants, including scouts, mentors, and organizers. The findings reveal that LT 3 effectively serves as a multicultural space by selecting a Christian-affiliated campsite, Mahanaim, which fosters tolerance and inclusivity among predominantly Muslim participants. Mentors and organizers played a pivotal role in instilling multicultural values, such as accommodating prayer times and promoting respectful communication. Additionally, cultural integration through traditional dances and games enriched participants' understanding of Indonesia's diversity. The study highlights the potential of scouting activities as a platform for multicultural education, offering practical recommendations for fostering inclusive youth development.